Beyond essce: reduction and history, philosophy and politics in Merleau-Ponty - Belvedere, Carlos Daniel (Estudios de Filosofía, 2007)
While discussing a letter from Husserl to Lévy Brühl, Merleau-Ponty states that the eidetic of history does not deliver us from historical investigation. This conception has always been present in his work, and it has been modeled in different ways and composing combinations along his phenomenology, his philosophy of history, and his ontology. In each one of those stages he displays, respectively, a situationist, a structuralist, and a sensible conception of the essence. However, the exceedence of the lived respect to the thought things does not have to be interpreted as a defeat of the thought but as creation.